2014
DOI: 10.1902/jop.2012.110620
|View full text |Cite
|
Sign up to set email alerts
|

Association of Leptin in Periodontitis and Acute Myocardial Infarction

Abstract: Elevated serum leptin concentration was associated with increased BMI, GCP, and AMI and may serve as a risk marker for these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(38 reference statements)
5
21
0
Order By: Relevance
“…Furthermore, leptin has contrasting effects on bone metabolism: an indirect, suppressive effect through the hypothalamus 29 or direct stimulation of osteoblast proliferation and differentiation and by prolonging the lifespan of primary osteoblasts 30 . Plasma/serum leptin concentrations increase during many inflammatory diseases including CP and cardiovascular disease 15‐20 . In the present study, the patients with CP had increased serum leptin concentrations, on average up to 11,600 pg/mL, which is in accordance with previous studies 15,16 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, leptin has contrasting effects on bone metabolism: an indirect, suppressive effect through the hypothalamus 29 or direct stimulation of osteoblast proliferation and differentiation and by prolonging the lifespan of primary osteoblasts 30 . Plasma/serum leptin concentrations increase during many inflammatory diseases including CP and cardiovascular disease 15‐20 . In the present study, the patients with CP had increased serum leptin concentrations, on average up to 11,600 pg/mL, which is in accordance with previous studies 15,16 .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, in serum/plasma, leptin concentrations were found to be higher in patients with CP, and non‐surgical periodontal therapy has been found to be effective in reducing leptin concentrations significantly 16 . Gundala et al concluded that elevated serum leptin concentrations in patients with CP could be considered a cardiovascular risk marker 17 . Longitudinal and cross‐sectional studies have shown positive associations between elevated serum leptin concentrations and cardiovascular risks including stroke, acute myocardial infarction, 18 chronic heart failure, 19 and coronary heart disease 20 …”
mentioning
confidence: 99%
“…The study performed by Ay et al enrolled both the CP and aggressive periodontitis (AP) groups [40]. The study performed by Gundala et al enrolled both the systemically healthy group and the acute myocardial infarction (AMI) group [47]. The study performed by Davies et al provided the data on male and female subjects separately [44].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, hyperleptinemia has also been identified as an independent risk factor for cardiovascular disease and myocardial infarction [37,38] directly linked to inflammation [39] and oxidative stress [3,35]. In the present study, we have found that leptin level increased proportionally with the degree of obesity (Table 2) and is positively correlated with adiposity (Pearson correlation with the percentage of fat mass r = 0.590, p < 0.001, data not shown), its serum concentration being similar to that previously reported by other authors [40,41].…”
Section: Discussionmentioning
confidence: 99%